Microarray analysis revealed dysregulation of multiple genes associated with chemoresistance to As 2O 3 and increased tumor aggressiveness in a newly established arsenic-resistant ovarian cancer cell line, OVCAR-3/AsR - Ong, P.-S. (2014)
10.1016/j.ejps.2011.12.003